Antarctic subglacial drilling rig: Part III. Drilling auxiliaries and environmental measures. Issue 84 (29th April 2021) - Fan, Xiaopeng; Talalay, Pavel; Sun, Youhong; Li, Xingchen; Zhang, Nan; Markov, Alexey; Yang, Yang; Cao, Pinlu; Wang, Rusheng; Liu, Yongwen; Liu, Yunchen; Wang, Ting; et al.
Abstract: The Antarctic subglacial drilling rig (ASDR) is designed to recover 105 mm-diameter ice cores up to 1400 m depth and 41.5 mm-diameter bedrock cores up to 2 m in length. In order to ensure safe and convenient drilling, drilling auxiliaries are designed to support fieldwork and servicing. These auxiliaries are subdivided into several systems for power supply, drill tripping in the borehole, ice core and chip processing, and drill servicing and maintenance. The required equipment also includes two generators, a drilling winch with a cable, logging winch with a cable, control desk, pipe handler with a fixed clamp, chip chamber vibrator, centrifuge, emergency devices and fitting and electrical tools. Additionally, several environmental protective measures such as a new liquid-tight casing with a thermal casing shoe and a bailing device for recovering drilling fluid from the borehole were designed. Most of the auxiliaries were tested during the summer of 2018–2019 near Zhongshan Station, East Antarctica while drilling to the bedrock to a depth of 198 m.